2024
DOI: 10.1590/1519-6984.256920
|View full text |Cite
|
Sign up to set email alerts
|

GCMS characterization and biological potential of the seeds and aerial part of Galium tricorne Stokes

Abstract: Natural products have long been proven very effective against various challenging diseases including cancer and bacterial infections. Galium tricorne is one of the important source of natural products, which has not been explored till date in spite of its profound ethnomedicinal prominence. The current study has been designed to explore the biological potential of G. tricorne and to extract and isolate chemical constituents from its aerial part and seeds respectively along with identification of their chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Also, M-Learning improves interaction and collaboration between students through mobile technology. The use of online communication platforms are concrete examples, such as Google Classroom that enables the exchange of information and collaboration in remote learning projects (Khan Academy, 2024;Google, 2024).…”
Section: Discussionmentioning
confidence: 99%
“…Also, M-Learning improves interaction and collaboration between students through mobile technology. The use of online communication platforms are concrete examples, such as Google Classroom that enables the exchange of information and collaboration in remote learning projects (Khan Academy, 2024;Google, 2024).…”
Section: Discussionmentioning
confidence: 99%
“…In 2023, Khan reported enantioselective amination of branched allylic carbonates using a molybdenum catalyst bearing DACH-derived (S,S)-L24 with up to 96% ee. 443…”
Section: Review Synthesismentioning
confidence: 99%
“…They found that GPT-3, primarily trained on English text, generated explanations that were significantly inferior to teacher-authored ones. Lately, Khan Academy has introduced a GPT-4 [1] powered tutoring system, Khanmigo [18], to assist teachers in planning their lessons and providing feedback on students writing. Our proposed approach, SimPal, is similar to Khanmigo in terms of assisting teachers in planning their lessons.…”
Section: Background and Related Workmentioning
confidence: 99%